Unveiling Islamophobia: the role of Daniel Pipes in the demonisation of the Muslims - Zakariya, Hafiz (2019)
This presentations describes the portrayal and misrepresentation of the Muslims as depicted by Daniel Pipes. First it describes the brief biography and advent of Daniel Pipes. The main focus of this lecture is Daniel Pipes' misrepresentations of the Muslims in his major writings especially after the advent of September 11, 2001/